1996
DOI: 10.1210/me.10.7.794
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic nuclear factor 3 is an accessory factor required for the stimulation of phosphoenolpyruvate carboxykinase gene transcription by glucocorticoids

Abstract: Transcription of the hepatic phosphoenolpyruvate carboxykinase gene is stimulated by glucocorticoids and inhibited by insulin. The glucocorticoid response is mediated by a complex glucocorticoid response unit that consists of two glucocorticoid receptor (GR)-binding sites (GR1 and GR2) and two accessory factor-binding sites (AF1 and AF2). The complete unit is required for the full glucocorticoid response. The dominant insulin effect is mediated in part through an insulin response sequence that is coincident wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…They showed that mutation of the FoxA binding site in a promoter-reporter construct severely attenuated gene activation by glucocorticoids. A similar situation was shown to exist for another fasting-activated gene, Pck1 , by Daryl Granner’s group [4143]. …”
Section: Foxa Factors and Nuclear Receptorssupporting
confidence: 59%
“…They showed that mutation of the FoxA binding site in a promoter-reporter construct severely attenuated gene activation by glucocorticoids. A similar situation was shown to exist for another fasting-activated gene, Pck1 , by Daryl Granner’s group [4143]. …”
Section: Foxa Factors and Nuclear Receptorssupporting
confidence: 59%
“…2D). C/EBP and HNF3alpha, two families of transcription factors whose binding motifs are highly represented in GBRs of glucocorticoid-activated genes, were previously shown to act with GR to participate in glucocorticoid-activate gene transcription [59], [60], [61], [62]. The HNF3alpha binding motif is similar to those of the FOX family transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, FoxO1 and FoxA2 play roles in hepatic glucose homeostasis by controlling gluconeogenic gene expression (3,4,37,39). Additionally, both transcription factors have been shown to be involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%